Comparison of different models for energy management strategy design of a parallel hybrid electric vehicle: Impact of the rotating masses - Abdoulaye Pam; Alain Bouscayrol; Philippe Fiani; Fabien Faval (IET Electrical Systems in Transportation)
Abstract Simulation is a key step during the development of energy management strategies (EMSs) for hybrid electric vehicles (HEVs). Moreover, optimal algorithms such as dynamic programming (DP) are used off‐line to define a benchmark for real‐time EMSs. However, several assumptions are made on the model to determine the appropriate energy management of an HEV. The rotating masses of the mechanical transmission, which are related to the vehicle dynamics, are often neglected for EMS development. In this study, different models for the EMS design of a parallel HEV are compared. An EMS based on the dynamical model that considers the rotating masses is used as a benchmark. A static model considering only the static mass of the vehicle is also studied. Intermediate models, such as an average gear model and an average mass model, are also considered. Simulations are performed using different driving cycles. The comparisons are based on the fuel consumption and also the computation time resulting from EMSs derived from the different models. Globally, the static model leads to an average error up to 20% on the energy consumption in comparison with the dynamical model. The average mass model leads to an error less than 1%. For real‐time simulations, the average mass model allows to reduce the computation time by a factor of 10 in comparison with the dynamical model.